Characteristics of Geological Conditions on Safety Factor (FK) of Open-Pit Slope and Landslide Mitigation at the Green Pit Location of Nickel Mining at PT. IFISHDECO Tb - Hasibuan, Parlindungan; Chaerul, Muhammad; Gusty, Sri (Dinasti Research, 2025)
The research location is within the IUP area of PT. IFISHDECO Tbk (122.168°–122.204° E and 4.371°–4.404° S), Tinanggea, South Konawe Regency, Southeast Sulawesi Province. This study aims to analyze the Safety Factor (SF) values of the slopes and the probability of landslide potential at the green pit mining slopes, as well as the landslide hazard mitigation map. The data used include engineering geological characteristics, topographic measurements obtained via total station, aerial photographs (drone), and rock mechanics sample test results. The SF analysis applied is the Simplified Bishop method with Mohr-Coulomb analysis, processed using Slide ver.6 software, along with landslide hazard potential maps and landslide hazard mitigation maps based on the Ministry of Energy and Mineral Resources of the Republic of Indonesia Decree (KEPMEN ESDM RI) No. 1827 K/30/MEM/2018.The research results are derived from slope stability analysis at the green pit mining site based on the static Safety Factor (SF) according to the rules of KEPMEN ESDM RI No. 1827 K/30/MEM/2018, which are as follows: - Single Slope Type: SF 0.91 - 1.26 (Unstable – Balanced) - Inter-ramp Slope Type: SF 1.15 - 1.25 (Balanced) - Overall Slope Type: SF 1.31 – 1.37 (Stable). The probability of soil movement (landslide) potential is 10 – 25%, with a medium severity landslide category. The medium severity landslide category applies when there are consequences such as serious human injuries, damage to facilities and infrastructure from 25% to 50%, production stoppages of more than 12 hours but less than 24 hours, buried reserves that can still be recovered, and environmental damage within the scope of the IUP area.The landslide hazard potential map is divided into three severity categories: low landslide severity, medium landslide severity, and high landslide severity. The landslide hazard mitigation map for the green pit open-pit mining site provides information on potential hazard zones covering an area of 0.33 hectares at the pit slope, safe zones covering 2 hectares outside mining activities, evacuation routes with distances ranging from 68 m to 267 m to the safe zone, and worker assembly points (muster points) equipped with emergency response facilities such as first-aid supplies, transportation means, mobilization facilities, and communication equipment, all of which are part of the mining safety management system.